Active Biodegradable Packaging Films Based on the Revalorization of Food-Grade Olive Oil Mill By-Products - Assamae Chabni; Celia Bañares; Irene Sanchez-Rey; Carlos F. Torres (Applied Sciences)
Synthetic packaging is being replaced by biodegradable packaging through the revalorization of food industry by-products. The olive oil (OO) industry, known for producing large quantities of antioxidant-rich by-products, can be a major supplier for sustainable packaging materials. This study aims to valorize a food-grade by-product (defatted flour, DF) from OO extraction produced using a zero-waste strategy that combines expeller press technology and supercritical CO2 extraction. DF and its aqueous extract (DFE) were combined with carboxymethylcellulose (CMC) to create biodegradable bioactive packaging films. DF contains a high content of insoluble dietary fiber (28.4%) and total phenolic compounds (35,000 ppm), including oleuropein, elenolic acid, hydroxytyrosol, and tyrosol (4324, 3603, 1525, and 157 ppm, respectively). This study examined the effects of DF and DFE on the physicochemical and barrier properties of the films, as well as their capacity to delay oxidation in polyunsaturated fatty acid-rich oil. Films with DF and DFE contained high phenolic content (1500 and 1200 ppm, respectively), and their inclusion improved ultraviolet visible barrier capacity. Additionally, oil oxidation was slower when protected by DF- and DFE-based films than when protected with CMC film alone. This allows their use as protective packaging and potential carriers of bioactive oils to enhance the nutritional and functional qualities of packaged foods.